Enhancing terahertz patch antenna performance with metamaterials for biomedical applications - Siraj Younes; Foshi Jaouad; Kaoutar Saidi Alaoui (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
This paper presents the performance enhancement of a terahertz (THz) patch antenna using the metamaterials (MTM). The antenna design features a rectangular patch with a modified ground structure, implemented on an FR4 substrate with dielectric properties of 4.4, a tan (δ) of 0.02, and a thickness of 1.6 µm. Operating at 4.92 THz, the antenna exhibits a -10 dB bandwidth of 0.25 THz (250 GHz), catering to diverse biomedical applications. To investigate the impact of incorporating MTM, the proposed MTM is positioned beneath the antenna at a separation of 12.8 µm. A comparative analysis of the antenna’s performance with and without MTM reveals a significant influence of MTM insertion. However, the results confirm the big influence of the addition of the MTM. As results, the return loss was improved from -23.16 dB to -44.73 dB. The gain was additionally elevated from 1.46 dB to 5.06 dB. The design and simulation of the antenna were carried out through high frequency structure simulator (HFSS) software.